Impacto socioeconómico de la contaminación de las playas de Lima - Iglesias León, Silvia (2000)
This article shows the results of the research project "Socio-Economic Impact of Pollution of Beaches in Lima" after monitoring water quality in 1999, carried out in five beaches (La Herradura, Agua Dulce, the Weeds and Makaha Marbella ). Marbella and Herradura were the most polluted beaches. They socioeconomic surveys conducted in different districts of Lima. 58% of respondents showed a preference to go to the beach in his free time during the weekends in the summer. Of these respondents, 71% preferred to go to the beaches of the South that the beaches of Lima, where he carried out the project, and this due to contamination.